Tracking of Formed Crystalline Phases in the Binary Silver Tellurite Glass-ceramics - El Zaibani, M. El Zaibani; Altawaf, A. Altawaf; El Agammyc, E. F. (Journal of Amran University, 2023)
Glasses and glass-ceramics based on silver tellurite system xAg2O·(100-x)TeO2 (0 £ x £ 60 mol%) were prepared by melt-quenching method. The structure of the studied glasses and glass-ceramics was investigated by several techniques. XRD patterns reveal the existence of only one glassy region at 20 < x ≤ 30 mol% with two crystalline a-TeO2 and Ag2TeO3 phases that formed separately in the prepared samples below 20 and beyond 30 mol% Ag2O, respectively. The peaks intensity corresponding to the crystalline a-TeO2 and Ag2TeO3 phases was found to decrease and increase with Ag2O content, respectively. This may be correlated with changes in the concentration of and units that, respectively, build up the crystalline a-TeO2 and Ag2TeO3 phases. In the glassy region, there is no crystalline phase, which may be attributed to the abundance of the deformed units that build up the glassy phase, and the concentrations of and units are neglected in this region. SEM and TEM micrographs and the related electron diffraction patterns (EDP) confirmed the formation of crystallized clusters in Ag2O-rich glasses.